Alcohol abstinence and mortality in a general population sample of adults in Germany: A cohort study - Ulrich John (Public Library of Science (PLoS), 2021)
Background Evidence suggests that people who abstain from alcohol have a higher mortality rate than those who drink low to moderate amounts. However, little is known about factors that might be causal for this finding. The objective was to analyze former alcohol or drug use disorders, risky drinking, tobacco smoking, and fair to poor health among persons who reported abstinence from alcohol drinking in the last 12 months before baseline in relation to total, cardiovascular, and cancer mortality 20 years later. Methods and findings A sample of residents aged 18 to 64 years had been drawn at random among the general population in northern Germany and a standardized interview conducted in the years 1996 to 1997. The baseline assessment included 4,093 persons (70.2% of those who had been eligible). Vital status and death certificate data were retrieved in the years 2017 and 2018. We found that among the alcohol-abstinent study participants at baseline (447), there were 405 (90.60%) former alcohol consumers. Of the abstainers, 322 (72.04%) had met one or more criteria for former alcohol or drug dependence or abuse, alcohol risky drinking, or had tried to cut down or to stop drinking, were daily smokers, or self-rated their health as fair to poor. Among the abstainers with one or more of these risk factors, 114 (35.40%) had an alcohol use disorder or risky alcohol consumption in their history. Another 161 (50.00%) did not have such an alcohol-related risk but were daily smokers. The 322 alcohol-abstinent study participants with one or more of the risk factors had a shorter time to death than those with low to moderate alcohol consumption. The Cox proportional hazard ratio (HR) was 2.44 (95% confidence interval (CI), 1.68 to 3.56) for persons who had one or more criteria for an alcohol or drug use disorder fulfilled in their history and after adjustment for age and sex. The 125 alcohol-abstinent persons without these risk factors (27.96% of the abstainers) did not show a statistically significant difference from low to moderate alcohol consumers in total, cardiovascular, and cancer mortality. Those who had stayed alcohol abstinent throughout their life before (42; 9.40% of the alcohol-abstinent study participants at baseline) had an HR 1.64 (CI 0.72 to 3.77) compared to low to moderate alcohol consumers after adjustment for age, sex, and tobacco smoking. Main limitations of this study include its reliance on self-reported data at baseline and the fact that only tobacco smoking was analyzed as a risky behavior alongside alcohol consumption. Conclusions The majority of the alcohol abstainers at baseline were former alcohol consumers and had risk factors that increased the likelihood of early death. Former alcohol use disorders, risky alcohol drinking, ever having smoked tobacco daily, and fair to poor health were associated with early death among alcohol abstainers. Those without an obvious history of these risk factors had a life expectancy similar to that of low to moderate alcohol consumers. The findings speak against recommendations to drink alcohol for health reasons. In this cohort study conducted over 20 years, Ulrich John and colleagues examine the relationship between alcohol abstinence and mortality in a German adult population. Author summary Why was this study done? According to evidence, alcohol abstinence seems to be associated with a lower life expectancy than low to moderate alcohol consumption. Individuals who abstain from alcohol might include those who have risk factors that can be reasons for the shorter life expectancy compared to low to moderate alcohol consumers. What did the researchers do and find? A random adult general population sample had been drawn and the study participants been inquired about their consumption of or abstinence from alcohol in a first contact. Twenty years later, proportions of deceased and time to death were determined and compared between former alcohol abstainers and low to moderate alcohol consumers among the 4,028 study participants. The findings show that 91% of the alcohol abstainers at first contact had consumed alcohol in life before and 72% had a history of one or more criteria of a former alcohol or drug use disorder, former risky alcohol consumption, efforts to cut down or to stop drinking, daily tobacco smoking, or fair to poor health. In terms of mortality rate, no statistically significant difference was apparent between alcohol abstinent persons without these risk factors and who had self-rated their health as good to excellent and persons who consumed low to moderate amounts of alcohol. What do these findings mean? Former alcohol use disorders, risky consumption, efforts to cut down on drinking, ever daily tobacco smoking, and fair to poor health may predict early death among alcohol abstainers. Healthy alcohol abstainers who have no alcohol- or tobacco-related risk factors may not have a higher mortality than low to moderate alcohol consumers. The findings speak against recommendations to drink alcohol for health reasons.